Teoria dos Jogos aplicada à coordenação de agentes, utilizando Teoria dos Valores de Troca - Pereira, Diego Rodrigues; Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
The Game Theory is a field in mathematics that studies the agent’s behavior in strategic situations, in which decision making affects all players involved. It provides several tools to model agent interactions in Multiagent Systems. Another tool to do this is the Exchange Values Theory, which model interactions between small groups of agents, that do services to each other. However, as the agents acts on its own and are self-interested, there are some problems to keep the exchange system in balance, requiring some regulation. In order to accomplish this, in this work we use Bayesian Games, or games with imperfect information, that allow us to represent uncertainty about the game being played. This can be represented by a probability distribution over the games. First we present a brief introduction on Game Theory’s concepts that are used here and then a Exchange Values Bayesian Game model, which allow us to regulate the exchanges made by the agents, without an external agent that regulates these interactions.